Philosophical Critique and Decoding Path of Rosa's New Alienation - Gan, Pengkun (Transactions on Social Science, Education and Humanities Research, 2024)
The theory of alienation occupies a very important position in Marx's theoretical system. In the Economic and Philosophic Manuscripts of 1844, Marx criticizes classical political economy in England starting from alienated labor and puts forward four aspects of alienated labor. The Frankfurt School further developed Marx's theory of alienation and conducted comprehensive investigations on technological alienation, cultural alienation, consumer alienation, and other aspects of modern society's culture, politics, and art. In the new turn of late modern society, the fourth generation Frankfurt School scholar Hartmut Rosa, starting from time analysis, analyzes the growth logic and dynamic stability of modern society's overall crisis through the theory of social acceleration critique, and proposes the social pathologies of "acceleration" and the solution of "resonance", attempting to achieve a better life for people in the present era through the adaptive mode of resonance theory. Based on Hartmut Rosa's works and related research, this article explores the theoretical origins of Rosa's theory of social acceleration critique, the historical background and ideological elements, elaborates on Rosa's analysis of the phenomenon of social acceleration, the new forms of alienation under the background of accelerated society, and the resonant solutions to the problem of new alienation. Finally, this article examines the theoretical value and shortcomings of his theory.